ANALYTICAL MODELS OF DRYING KINETICS OF WALNUTS AND PARTS OF PLANT MASS TAKING INTO ACCOUNT THE GEOMETRY OF THE MATERIAL - STADNIK, MYKOLA; LUTS, PAVLO; РУТКЕВИЧ, ВОЛОДИМИР; KONDUS, VLADYSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the kinetics of drying of vegetative parts of plant materials of various shapes in order to determine the drying time and exposure of the process for optimizing post-harvest processing. The peculiarities of moisture transport in materials of complex structure and the impossibility of accurately taking into account all mass and heat transfer factors are considered. Infrared drying allows you to reach the final moisture content faster, keeping the core from overheating. The use of simplified analytical models based on mass conductivity equations for bodies of classical geometric shape (plate, cylinder, sphere) with boundary conditions of the third kind is proposed. The use of the mass formation level for those classical forms, taking into account the boundary conditions of the third kind, allows for effective prediction of the mass transfer process in heterogeneous plant materials and influencing the drying rate of the physical form of a part of the material. The obtained formulas for calculating the drying time and changes in the moisture content of the material can be used to optimize the modes of convective, vacuum and infrared drying, which ensures energy savings and improved quality of the final product. For walnuts, kinetic dependences of drying by convective and infrared methods are given, demonstrating the influence of temperature, humidity and physical shape on the speed of the process. The obtained simplified analytical formulas allow determining the change in the moisture content of the material over time and calculating the drying exposure for plant parts of various shapes, providing a scientifically sound basis for optimizing drying modes and improving the quality of the final product.
Keywords: walnuts; humidity; drying agent; drying chamber; coolant speed; temperature; fan; energy efficiency